已知在等比数列 $\left\{a_n\right\}$ 中, $a_1+a_2=4$, 且 $a_1, a_2+2, a_3$ 成等差数列, 数列 $\left\{b_n\right\}$ 满足 $b_n > 0, b_1=$ $1, b_{n+1}^2-b_n^2=2\left(b_{n+1}+b_n\right)$.
(1) 求 $\left\{a_n\right\}$ 的通项公式;
(2) 设 $c_n=2^{b_n}-a_n$, 求数列 $\left\{c_n\right\}$ 的前 $n$ 项和 $T_n$.
【答案】 解(1)以为你 $a_1, a_2+2,a_3$ 成等差数列,所以 $a_1+a_3=2(a_2+2)$
又因为 $a_1+a_2=4$, 所以, $a_3=3 a_2$, 得 $\left\{a_n\right\}$ 的公比 $q=3$,
所以 $a_1+3 a_1 =4$, 解得 $a_1=1$,
故 $a_n=3^{n-1}$.



(2) 由 $b_n > 0, b_{n+1}^2-b_n^2=2\left(b_{n+1}+b_n\right)$, 得 $b_{n+1}-b_n=2$,
则 $\left\{b_n\right\}$ 是等差数列, 因为 $b_1=1$, 所以 $b_n=2 n-1$,
则 $c_n=2^{b_n}-a_n=2^{2 n} 1-3^n 1$,
则 $T_n=\left(2^1-3^0\right)+\left(2^3-3^1\right)+\left(2^5-3^2\right)+\cdots+\left(2^{2 n}{ }^1-3^n{ }^1\right)$
$$
\begin{aligned}
&=\left(2^1+2^3+2^5+\cdots+2^{2 n}{ }^1\right)-\left(3^0+3^1+3^2+\cdots+3^n{ }^1\right) \\
&=\frac{2\left(1-4^n\right)}{1-4}-\frac{1-3^n}{1-3} \\
&=\frac{4^{n+1}-3^{n+1}-1}{6} \text {. } \\
&
\end{aligned}
$$


系统推荐